Left atrial strain and clinical outcome in patients with significant mitral regurgitation after surgical mitral valve repair - Kim, Se-Eun; Kim, Dae-Young; Seo, Jiwon; Cho, Iksung; Hong, Geu-Ru; Ha, Jong-Won; Shim, Chi Young (Frontiers in Cardiovascular Medicine, 2022)
Background: This study aimed to investigate the prognostic value of left atrial (LA) strain in patients with significant mitral regurgitation (MR) after surgical mitral valve (MV) repair. Methods: A total of 169 patients (age 55 ± 15 years, 88 men) with moderate or severe MR on echocardiogram at least 6 months after surgical MV repair for primary MR were studied. Two-dimensional, Doppler, and speckle tracking echocardiography including MR quantitative measures, chamber size, and LA strain were comprehensively analyzed. The primary outcome was a composite of cardiovascular death, heart failure hospitalization, and MV reoperation. Results: During a median of 44.4 months [interquartile range (IQR): 18.7-70.3 months] of follow-up, 44 patients (26%) experienced clinical events; these patients had greater MR volume, elevated mean diastolic pressure gradient and pulmonary artery systolic pressure, and enlarged chamber size compared with patients who did not experience events. Patients with events showed significantly lower LA strain [13.3% (IQR: 9.3-23.8%) vs. 24.0% (IQR: 13.1-31.4%), p=0.003] and higher MR volume/LA strain [3.09ml/% (IQR: 2.06-5.80ml/%) vs. 1.57ml/% (IQR: 1.04-2.72ml/%), p<0.001] than those without events. MR volume/LA strain was a good predictor of clinical outcomes (cut-off 1.57ml/%, area under the curve 0.754, p<0.001). On multivariable Cox proportional analysis, MR volume/LA strain was independently associated with clinical outcomes (hazard ratio: 1.269, 95% confidence interval: 1.109-1.452, p<0.001) along with pulmonary artery systolic pressure. Conclusions: A measure of LA mechanical function relative to MR volume is associated with clinical outcomes in patients with significant MR after surgical MV repair.